Diseño de instrumento para evaluar conocimientos, actitudes y prácticas sobre caninos impactados en odontólogos (2022)
The knowledge, attitudes, and practices (KAP) have been evaluated to bring intangible concepts to a dimension where they can be measured, counted and give results. The objective of this research was to develop an instrument that allows measuring the CAP presented by general dentists regarding the diagnosis and preventive management of impacted canines. The questions were made from a review of the available literature, of the important findings in the clinical and radiographic diagnosis, remission and treatment of impacted canines. To build the instrument, a bibliography search was carried out, some questions were created, the experts were chosen, the questions were sent to evaluate the relevance, coherence, consistency and validity of the instrument, definitions were achieved during the phases of questions, and they were chosen. The questions will allow to measure the CAP of general dentists about the diagnosis and management of impacted canines, in this way an adequate instrument was obtained for its implementation in future investigations.